ApaI Vitamin D Receptor Gene Polymorphisms in Psoriasis - Oentari, Widyaningsih; Roesyanto-Mahadi, Irma D; Siregar, Yahwardiah (Universitas Muhammadiyah Sumatera Utara, 2021)
Psoriasis is a chronic autoimmune skin disorder that is an autoimmune disease and still considers a global problem. This condition is suspected to be contributed by genetic and environmental factors. Several studies have shown an association between vitamin D gene receptor polymorphisms and the risk of psoriasis. This study was an observational study, which involved 64 research subjects, who were psoriasis patients. Each subject was interviewed and went through physical examination, also Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) examination to determine ApaI (rs7975232) vitamin D receptor gene polymorphism. After the tabulation of the data, we found that the age of psoriasis onset in this study was 21 to 40 years old with an average of 34.40 14.98 years old. The majority of our subjects ApaI VDR gene polymorphism genotype was aa (53.1%). This is consistent with the results of several studies conducted in Asia.